1986
DOI: 10.1007/bf02374222
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia excretion byAzotobacter chroococcum in liquid culture and soil in the presence of manganese and clay minerals

Abstract: Summary Ammonia excretion was studied in the presence of Mn §247 in liquid culture and soil with amendments of the minerals using two ammonia excreting strains of Azotobacter chroococcum (AC2 and AC50) and a non-excreting strain (AC45) under sterilized as well as unsterilized conditions. Ammonia excretion increased in the presence of 1 • 10-~M Mn * § in liquid culture as well as in soil. But there was a decrease in ammonia excretion with increasing clay content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 3 publications
3
15
0
Order By: Relevance
“…In addition, another important characteristic of Azotobacter associated with plant improvement is excretion of ammonia in the rhizosphere in the presence of root exudates (Narula and Gupta, 1986), which could explain why the dual inoculation treatments with bacteria and AMF resulted in a slightly higher ( pN0.05) total N content in soil (Fig. 3) compared to those with AMF inoculation only.…”
Section: Soil Propertiesmentioning
confidence: 98%
“…In addition, another important characteristic of Azotobacter associated with plant improvement is excretion of ammonia in the rhizosphere in the presence of root exudates (Narula and Gupta, 1986), which could explain why the dual inoculation treatments with bacteria and AMF resulted in a slightly higher ( pN0.05) total N content in soil (Fig. 3) compared to those with AMF inoculation only.…”
Section: Soil Propertiesmentioning
confidence: 98%
“…In addition to the source of nitrogen in soil its involvement in antagonistic interactions with soil pathogens that result in disease control is reported (Saraf et al, 2008). Narula and Gupta (1986) found that inoculation of wheat and barley with ammonia excreting strains caused increased dry weight and enzyme activity.…”
Section: Stress (Salt and Ph) Tolerant Pgprmentioning
confidence: 99%
“…The main agents of biofertilizers are Azotobacter, Azospirillum, blue green algae, Azolla, P-solubilizing microorganisms and mycorrhizae [19]. However, apart from providing N to plants, Azotobacter promotes plant growth directly by secreting considerable amounts of biologically active substances like B vitamins, nicotinic acid, pantothenic acid, biotin, gibberellic acid, Indole-3 Acetic Acid (IAA) and cytokinin [20][21][22] and ammonia [23] or indirectly by protecting the plant from diseases [24]. Hence, a trial was performed to study the effect of bio-fertilizer on plant growth, yield and linked protein content changes in black gram.…”
Section: Introductionmentioning
confidence: 99%